Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/antiox10081274
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Mitochondrial Oxidative Stress and Endoplasmic Reticulum Stress in Cardiovascular Fibrosis in Obese Rats

Abstract: We have evaluated the role of mitochondrial oxidative stress and its association with endoplasmic reticulum (ER) stress activation in the progression of obesity-related cardiovascular fibrosis. MitoQ (200 µM) was orally administered for 7 weeks to male Wistar rats that were fed a high-fat diet (HFD, 35% fat) or a control diet (CT, 3.5% fat). Obese animals presented cardiovascular fibrosis accompanied by increased levels of extracellular matrix proteins and profibrotic mediators. These alterations were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 70 publications
(77 reference statements)
1
20
0
Order By: Relevance
“…The overexpression of UPR components, such as CHOP and ATF4, directly contribute to ROS synthesis in the ER [ 33 ]. Moreover, the impaired ER can translate Ca 2+ to mitochondria through the calcium release channel and mitochondrial-associated membranes, which exaggerates the production of ROS via the electron transport chain (ETC) [ 46 ]. In the present study, the expression of CHOP and ATF4 were downregulated by dietary 4-PBA.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of UPR components, such as CHOP and ATF4, directly contribute to ROS synthesis in the ER [ 33 ]. Moreover, the impaired ER can translate Ca 2+ to mitochondria through the calcium release channel and mitochondrial-associated membranes, which exaggerates the production of ROS via the electron transport chain (ETC) [ 46 ]. In the present study, the expression of CHOP and ATF4 were downregulated by dietary 4-PBA.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to further examine the influence of Nrf2 on cell death, another study suggests that its elicitation might be related to mitochondrial DNA depletion in HCC cell lines [ 89 ]. It has been previously demonstrated that there is an underlying relationship between mtDNA and ER stress, suggesting that any disturbance in the ER could have an impact on mtDNA and vice versa [ 90 , 91 , 92 ]. Investigating the crosstalk between ER stress and mtDNA depletion could then provide precious insights to further assess chemoresistance mechanisms in HCC in relation to cell death [ 92 ], especially as mtDNA depletion was also found to trigger other markers such as survivin, Bax, and Bcl2, which, when imbalanced, hinder pro-apoptotic signals [ 89 ].…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%
“…Significant association of antioxidant defense parameters with anthropometric, lipid, and inflammatory markers has also been shown in obese young adults with increased risk of cardiovascular diseases [69,70]. In addition, the latest advances in the field of obesity-related OxS biology are explorations regarding telomere length [71] and mitochondrial OxS [72,73]. It shows that telomeres shorten according to the length of obesity phenotype and also to the degree of OxS influenced by obesity [71].…”
Section: Aos In Obesity and Irmentioning
confidence: 99%
“…It shows that telomeres shorten according to the length of obesity phenotype and also to the degree of OxS influenced by obesity [71]. Furthermore, recent studies show the relevance of mitochondrial OxS in metabolic alterations associated with obesity and mitochondrial OxS in the dysbiosis associated with a high-fat diet (HFD) in rats [72,73].…”
Section: Aos In Obesity and Irmentioning
confidence: 99%